Die Schule der Janitscharen - Twardecki, Alojzy 1938-2016 (Lang-Ed, 2013)
Christoph Koch met Alojzy Twardecki in 1974 and over the years became fascinated by the Pole's story of survival and triumph over victimization by the Nazi's Lebensborn program. In the 1960s and 1970s, Twardecki's work was published by various Polish presses. In this German translation, Koch has contributed a 50-page preface, providing pertinent information into the Nazi's policy on racial purity in combination with ethnic cleansing